Formation and Mechanism of Magnesium Titanate in the Process of Ilmenite Reduction. (3rd April 2021) - Chen, Chao; Sun, Tichang; Geng, Chao; Kou, Jue; Liu, Jianguo
ABSTRACT: In this study, magnesium titanate was prepared through the high-temperature reaction of ilmenite and MgO in a reducing atmosphere, and its formation process and mechanism under different conditions were investigated. The results showed that a reducing atmosphere is necessary to prepare magnesium titanate. Although Mg could replace Fe and form magnesium titanate without reductant, the generated magnesium titanate contained large amounts of iron. While a reducing atmosphere promoted the formation of magnesium titanate and accelerated the reaction rate, this is because iron oxide in the reaction system is reduced to metal Fe under a reducing atmosphere. The effect of iron reduction improved, the content of iron in the magnesium titanate decreased with increasing temperature, and pure particles of magnesium titanate were generated at 1450°C. Magnesium titanate was transformed along MgTi2 O5 →MgTiO3 →Mg2 TiO4 path with increasing MgO dosage. The magnesium titanate product, contains above 90% Mg2 TiO4, was obtained by grinding and magnetic separation as non-magnetic product.